Expanding the reach of a fall prevention intervention for older adult emergency department patients through telehealth: a trial protocol - Keleman, Audrey; Bounds, Megan; Mundo, William; Gomez-Picazo, Jonathan; Mealer, Meredith; Linnebur, Sunny A.; Ferozan, Bucky; Dunn, Julie; Stevens-Lapsley, Jennifer; Goldberg, Elizabeth (Frontiers in Public Health, 2025)
BackgroundFalls are a leading cause of emergency department (ED) visits among older adults, yet many patients are discharged without a clear understanding of their fall risk factors or access to timely prevention services. The Geriatric Acute and Post-Acute Fall Prevention (GAPcare) intervention has demonstrated efficacy in reducing fall-related ED revisits by addressing these factors during the ED visit. Still, its reliance on in-person specialists limits scalability to smaller and lower-resourced EDs.MethodsThis study outlines a protocol for adapting GAPcare into a telehealth-enabled model (e-GAPcare) using a two-phase implementation science approach. Phase 1 engages ED staff, patients, and caregivers in structured workgroups to guide the adaptation of telehealth while preserving core intervention components. Phase 2 involves a single-arm trial at one ED with 40 older adults presenting after a fall, evaluating feasibility and acceptability. The intervention includes remote consultations with a pharmacist and physical therapist, tailored assessments to address individual fall risk factors, and a standardized checklist integrated into discharge planning that is shared with primary care clinicians.OutcomesData will be collected through surveys and electronic health records over a 6-month follow-up period. Trial outcomes include usability, care transition quality, healthcare utilization, and uptake of recommendations.ConclusionBy leveraging hospital-based telehealth infrastructure and eliciting end-user perspectives on needed adaptations, e-GAPcare aims to extend the reach of evidence-based fall prevention programs to smaller EDs or those that lack in-person pharmacists and physical therapists.